Analysis of Pediatric Hand Injuries Presenting at A Public Sector Tertiary Care Hospital In Karachi, Pakistan - Naz, Erum; Ali Khan, Faisal Akhlaq; Zulfiqar, Bushra; Farrukh, Rabeeaa; Kiran, Saba; Chhotani, Saira Ahmed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the pattern of pediatric hand injuries presenting at a public sector tertiary care hospital in Karachi.Study Design: Cross-sectional studyPlace and Duration of Study: Department of Plastic Surgery, Ruth Pfau Civil Hospital, Karachi Pakistan from Mar to Aug 2022.Methodology: Children of age 1 to 17 years of either gender, presenting to emergency room within 24 hours of hand injury were enlisted into this study. Patients with poly-trauma and those whose parents did not give consent for participation were not invited to be the study part. Patient’s age, gender, residence, injured hand, zone and sites and mode of injury was recorded in the pre-designed structured proforma.Results: Four hundred and thirty four (n=434) patients were enrolled into the study with median age of 6 (IQR=2-10) years. Majority of children were males 253 (58.3%), had injury in single zone 385 (87.8%). Sixty-eight (15.8%) patients had more than single injury site. The most frequent injury mode was door injury 126 (29%) followed by machine injury 109 (25.1%) injury from sharp object 78 (18%), road traffic accidents 57 (13.1%), fall 31 (7.1%), blunt trauma 25 (5.8%) and gunshot 8 (1.8%). Only skin laceration injury was present in nearly quarter of the hand injuries 120 (27.6%) whereas fractures 141 (32.5%) and tendon injury 147 (33.9%) was present in about one-third of the total cases.Conclusion: The present study analyzed that children of age groups 1-10 years are commonly affected with hand injuries. All of the causes of hand inju....